History of vocational education in Brasil and its relationship with the work principle (Research, Society and Development, 2022)
This article seeks to present important points about the history of Vocational Education in Brazil, as well as a succinct but necessary approach to work as an educational principle. As a methodology, we used bibliographic and documental research (Gil, 2010). Initially, we will present the most important points about the emergence and consolidation of Brazilian Vocational Education, having as a time frame normative created and structures of professional education implemented over several years, from the beginning of the 19th century to the present day. Therefore, we will analyze the concept of work-related professional education as an educational principle. For this to be possible, we will approach this principle related to the concept of work, in a historical and ontological perspective, all this being part of a unit of conception of work. Furthermore, we will study the educational principle of work, emerging concepts and debating the dichotomy between fact (obviousness of the object of work) and principle (work as a human element that allows it to transform nature to meet its needs). In this analytical outline, we seek to understand work as an educational principle in a perspective that composes the fundamental conceptions of professional education, considering it as the essence of life and human formation and as an essential element for its self-recognition as a founding part of a social construction, cultural and collective.